Complete revascularization in stable multivessel coronary artery disease: A real world analysis from the British Columbia Cardiac Registry. Issue 3 (4th March 2021) - Iqbal, M. Bilal; Moore, Peter T.; Nadra, Imad J.; Robinson, Simon D.; Fretz, Eric; Ding, Lillian; Fung, Anthony; Aymong, Eve; Chan, Albert W.; Hodge, Steven; Webb, John; Sheth, Tej; et al.
Abstract: Background: More than half of patients undergoing percutaneous coronary intervention (PCI) have multivessel disease (MVD). The prognostic significance of PCI in stable patients has recently been debated, but little data exists about the potential benefit of complete revascularization (CR) in stable MVD. We investigated the prognostic benefit of CR in patients undergoing PCI for stable disease. Methods: We compared CR versus incomplete revascularization (IR) in 8, 436 patients with MVD. The primary outcome was all‐cause mortality at 5 years. Results: A total of 1, 399 patients (17%) underwent CR during the index PCI procedure for stable disease. CR was associated with lower mortality (6.2 vs. 10.7%, p < .001) and lower repeat revascularization at 5 years (12.7 vs. 18.4%, p < .001). Multivariable‐adjusted analyses indicated that CR was associated with lower mortality (HR = 0.73, 95% CI: 0.58–0.91, p = .005) and repeat revascularization at 5 years (HR = 0.78, 95% CI: 0.66–0.93, p = .005). These findings were also confirmed in propensity‐matched cohorts. Subgroup analyses indicated that CR conferred survival in older patients, male patients, absence of renal disease, greater angina (CCS Class III‐IV) and heart failure (NYHA Class III‐IV) symptoms, and greater burden of coronary disease. In sensitivity analyses where patients with subsequent repeat revascularization events were excluded, CR remained a strong predictor for lower mortality (HR = 0.69, 95% CI: 0.54–0.89, p = .004). Conclusions: In this study of stable patients with MVD, CR was an independent predictor of long‐term survival. This benefit was specifically seen in higher risk patient groups and indicates that CR may benefit selected stable patients with MVD.